A Retrospective Study on Amoxicillin Susceptibility in Severe Haemophilus influenzae Pneumonia. (10th September 2020) - Danneels, Pierre; Postorino, Maria Concetta; Strazzulla, Alessio; Belfeki, Nabil; Pitch, Aurelia; Pourcine, Frank; Jochmans, Sebastien; Dubée, Vincent; Monchi, Mehran; Diamantis, Sylvain
Abstract : Introduction . Treatment of Haemophilus influenzae (Hi) pneumonia is on concern because resistance to amoxicillin is largely diffused. This study describes the evolution of resistance to amoxicillin and amoxicillin/clavulanic acid (AMC) in Hi isolates and characteristics of patients with Hi severe pneumonia. Methods . A monocentric retrospective observational study including patients from 2008 to 2017 with severe pneumonia hospitalized in ICU. Evolution of amoxicillin and AMC susceptibility was showed. Characteristics of patients with Hi pneumonia were compared to characteristics of patients with Streptococcus pneumoniae (Sp) pneumonia, as reference. Risk factors for amoxicillin resistance in Hi were investigated. Results . Overall, 113 patients with Hi and 132 with Sp pneumonia were included. The percentages of AMC resistance among Hi strains decreased over the years (from 10% in 2008-2009 to 0% in 2016-2017) while resistance to amoxicillin remained stable at 20%. Also, percentages of Sp resistant strains for amoxicillin decreased over years (from 25% to 3%). Patients with Hi pneumonia experienced higher prevalence of bronchitis (18% vs. 8%, p = 0.02, chronic obstructive pulmonary disease (43% vs. 30% p = 0.03 ), HAP (18% vs. 7%, p = 0.01, ventilator-associated pneumonia (27% vs. 17%, p = 0.04, and longer duration of mechanical ventilation (8 days vs. 6 days, p = 0.04 ) than patients with Sp pneumonia. Patients with Sp pneumonia had more frequently local complications than patients with Hi pneumonia (17% vs. 7%, p = 0.03 ). De-escalation of antibiotics was more frequent in patients with Sp than in patients with Hi (67% vs. 53%, p = 0.03 ). No risk factors were associated with amoxicillin resistance among patients with Hi pneumonia. Conclusions . Amoxicillin resistance was stable over time, but no risk factors were detected. AMC resistance was extremely low, suggesting that AMC could be used for empiric treatment of Hi pneumonia, as well as other molecules, namely, cephalosporins. Patients with Hi pneumonia had more pulmonary comorbidities and severe diseases than patients with Sp pneumonia.